CONTROL OF VALVE ELECTRIC DRIVE COORDINATES OF AUTOMATED WELDING EQUIPMENT FEED MECHANISMS - V. A. Lebedev (National Technical University "Kharkiv Polytechnic Institute", 2020)
Goal. Finding ways to improve the quality of operation of the electrode wire feeder in terms of increasing the frequency of undistorted pulse feed with controlled characteristics, in particular its speed, as well as developing methods to simplify the adjustment of regulators of fast-acting electric drive to improve the results of the arc welding and surfacing process. Methodology. In the work, methods of analysis of existing technical solutions were used to increase the speed of operation of electric drives for a specific purpose with the choice of the most rational solution based on the use of the method of synthesis of a control system based on the concept of inverse problems of dynamics with subsequent computer simulation, confirming the adequacy of the applied method of synthesis of high-speed systems. Results. The authors considered the possibilities of increasing the speed of control systems for gearless computerized electric drives in a system with modern designs of valve electric drives for electrode wire feeding systems. A mathematical model of a rectifier motor has been developed with some assumptions that significantly influenced the simulation results. The new possibilities are based on the use of an original synthesis method based on the use of the concept of the inverse problem of dynamics with the subsequent study of the operation of the automatic control system for pulse wire feed, which was performed with aperiodic adjustment of the velocity contour by different methods. This approach made it possible to obtain the necessary laws of electric drive control without the traditional solution of the optimization problem. The developed control system for the electrode wire feed with pulsed motion algorithms provided the required linear movement of the wire at a pulse repetition rate of 100 Hz. The carried out computer simulation of the new control system confirmed the results of the study. It was found that an increase in the pulse time duration over 50 % of the pulse repetition period for given feed frequencies leads to an increase in the wire movement in the pulse, as well as to a decrease in the worked out frequency of the wire linear displacement feed. It was not possible to provide the required wire movement in the impulse feed mode for aperiodic adjustment of the speed loop with a P-controller for the same system parameters. Originality. The development was carried out for a specific application in the electrode wire feed systems of mechanized and automatic equipment for consumable electrode arc welding with obtaining certain algorithms of pulse motion. To effectively solve the complex problem of increasing the frequency of feed pulses with the provision of a displacement step, an original technique of the concept of inverse dynamic problems with confirmation of the result by mathematical modeling by practical results was used. Practical significance. The use of standard settings of the valve electric drive of mechanized and automatic welding equipment provides the frequency of undistorted electrode wire feed in the pulse mode of the feed mechanisms up to 50 Hz. New possibilities of settings made it possible to increase the frequency of wire feed, which makes it possible to raise the quality indicators of welded products - the formation of a welded joint, a decrease in electrode metal losses, an increase in the mechanical properties of a welded joint.